2018
DOI: 10.1130/g45206.1
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete but intricately detailed: The inevitable preservation of true substrates in a time-deficient stratigraphic record

Abstract: True substrates are defined as sedimentary bedding planes that demonstrably existed at the sediment-water or sediment-air interface at the time of deposition, as evidenced by features such as ripple marks or trace fossils. Here we describe true substrates from the Silurian Tumblagooda Sandstone of Western Australia, which have been identified by the presence of the surficial trace fossil Psammich nites. The examples are unexpected because they have developed along erosional internal bounding surfaces within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…The facies characteristics resemble wave-influenced and tide-influenced mouth bars in the Sego Sandstone (FA 4 in Legler et al, 2014). Ichnological characteristics are consistent with some physical and/or chemical stresses during mixed-energy inshore deposition, including possible intermittent colonization of sedimentary surfaces (Davies & Shillito, 2018). Consequently, FA 4 is interpreted as storm-reworked, fluvial-influenced mouth bars with possible tide influence.…”
Section: Discussionmentioning
confidence: 68%
“…The facies characteristics resemble wave-influenced and tide-influenced mouth bars in the Sego Sandstone (FA 4 in Legler et al, 2014). Ichnological characteristics are consistent with some physical and/or chemical stresses during mixed-energy inshore deposition, including possible intermittent colonization of sedimentary surfaces (Davies & Shillito, 2018). Consequently, FA 4 is interpreted as storm-reworked, fluvial-influenced mouth bars with possible tide influence.…”
Section: Discussionmentioning
confidence: 68%
“…Experiments have demonstrated that the combination of the two can lead to enhanced survivorship of arthropod trackways over those made in dry sand or sand with just surface moisture or the presence of clay minerals alone . Nevertheless, it has been recently argued that special conditions are not necessarily needed to preserve such trace fossils (see Davies & Shillito, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the existence of traces on eroded bounding surfaces in the BVG (e.g., flute marks; our figure DR6 in the GSA Data Repository) proves that they had a high preservational potential, even within an erosive setting. This is not unexpected because, contrary to traditional models (e.g., Seilacher, 2008), trackway preservation is probable under many spatially heterogenous, but otherwise mundane, sedimentary conditions (Davies and Shillito, 2018).…”
mentioning
confidence: 60%